Visual forms of the mahkota on the Melaka Traditional Mosque / Raziq Abdul Samat, Shafirah Shaari and Ahmadrashidi Hasan - Abdul Samat, Raziq; Shaari, Shafirah; Hasan, Ahmadrashidi (2012)
Melaka has a unique diversity of heritage and culture and has been listed as World Heritage City by the UNESCO in 2008. According on the history facts, Melaka was known as the region's most important entreport in the 14th century for its strategic location as a trade route between India and China. Therefore, Melaka was populated by the merchants from all over the world especially from China, India, Indonesia and Persia. These merchants brought along their culture of the origin. The assimilation of the cultures especially Chinese, Javanese and Indian influences can be seen on the historical building in Melaka One of the architectural elements believed which have been influenced by these cultures is the mahkota. Mahkota which is located at the top of the roof structure became very popular among building in Melaka especially the mosque. Mahkota can be defined as a decoration which can be seen on the top of Malay-Archipelago pyramidal roof. This research is study the formalistic elements of visual and principle of design on the mahkota. Four of the oldest Melaka traditional mosque had been choosen as research sample and there are Masjid Kg Hulu, Masjid Tengkera, Masjid Kg Kling and Masjid Pengkalan Rama. Design analysis method will be use to analyzed the visual of the mahkota. There are several aspect will be analyze such as shape, colour, composition, unity, balance and others which is related. Findings showed that mahkota was used as stupa in other beliefs such as Buddha and Hindu. Finding also showed that the mahkota was designed with the awareness of design principles such as balance, harmony and unity. The uses of repetition, intricate design motifs, stylization of nature were evidence in producing an artistic pattern design of the mahkota.